Benefice and pitfall of direct oral anticoagulants in very high-risk myeloproliferative neoplasms. Issue 216 (August 2022) - Herbreteau, Laura; Papageorgiou, Loula; Le Clech, Lenaïg; Garcia, Geoffrey; James, Chloé; Pan-Petesch, Brigitte; Couturaud, Francis; Gerotziafas, Grigorios; Lippert, Eric; Ianotto, Jean-Christophe
Abstract: Introduction: Direct oral anticoagulants (DOACs) have recently proven their efficacy and safety, as primary and secondary prevention agents for thrombosis in cancer patients. We aimed to determine if DOACs might be a suitable choice to reduce the thrombotic risk in myeloproliferative neoplasm (MPN) patients. Materials and methods: We analysed a large multicentric cohort of MPN patients treated with rivaroxaban or apixaban after atrial fibrillation (AF) or thrombotic events. Results: We included 135 MPN patients with a median follow-up of 23.8 months since DOAC initiation. Twenty patients (14.8 %) developed 30 thrombotic events (28 arterial thromboses in 19 patients) for a global incidence of 6.5 % patient-years. No difference was highlighted between apixaban and rivaroxaban in terms of thrombosis risk, but the incidence of arterial thrombosis was significantly higher on low-dose DOACs (11.9 vs. 4.5 % patient-years, p = 0.04). Bleeding events were more frequent in the full-dose group (41.2 vs. 15.2 %, p = 0.006). However, major and clinically relevant non major (CRNM) bleeding events occurred in 18 patients (13.3 %), with no difference between the groups. Age was the only identified thrombotic risk factor, whereas risk factors for major or CRNM bleeding were a full-dose treatment regimen and a combination of DOAC/low-dose aspirin. Conclusions: DOACs seem effective in preventing venous thrombosis in MPN patients with AF or VTE. For these high-risk patients, low-dose DOACs exposed patients to more arterial thrombosis but fewer bleeding events. Prospective studies are needed to evaluate and compare DOACs to the currently recommended antithrombotic drugs for high-risk MPN patients.